Assessing the Influence of Public Relation Strategy, Digital Marketing, and Brand Awareness on Customer Loyalty (International Forum of Researchers and Lecturers, 2023)
This qualitative study aims to delve into the intricate interplay between public relation strategy, digital marketing, brand awareness, and their influence on customer loyalty. Employing a qualitative research approach, the study will utilize in-depth interviews and focus group discussions to gather rich insights from participants. A purposive sampling technique will be employed to select participants who possess relevant experiences and perspectives in the domain of interest. Data analysis will involve thematic analysis, allowing for the identification of recurring themes and patterns within the data. The findings of this research endeavor are anticipated to shed light on the nuanced relationships between the aforementioned factors and customer loyalty, offering valuable insights for businesses seeking to enhance customer retention strategies in today's competitive landscape.